Health-related quality of life in persons post-COVID-19 infection in comparison to normative controls and chronic pain patients - Moens, Maarten; Duarte, Rui V.; De Smedt, Ann; Putman, Koen; Callens, Jonas; Billot, Maxime; Roulaud, Manuel; Rigoard, Philippe; Goudman, Lisa (Frontiers in Public Health, 2022)
The Coronavirus disease 2019 (COVID-19) pandemic exerted a tremendous pressure on the healthcare system, people's social life, mental health and financial status with profound implications for the general population. The exact impact of the pandemic on the overall physical, mental and social wellbeing of COVID-19 infection survivors on the long term has not yet been explored in a thorough way. Based on the reporting of persistent pain, fatigue and dyspnea symptoms by these survivors, it is our hypothesis that their quality of life will be extremely impacted, as is observed in patients with chronic pain. Therefore, the first aim of this study was to perform an in-depth evaluation of the quality of life of post-COVID-19 infected persons. The second aim was to compare the quality of life of these persons with a normative population and with patients with chronic pain. Health-related quality of life, as a measure for a person's overall physical, mental, and social wellbeing, was measured with the 3-level EQ5D in 547 post-COVID-19 infected persons. These data were compared to reference data from normal population records for Belgium and to data from patients with chronic pain after spinal surgery with two-way analyses of variance. In total, 89.58% of the post-COVID-19 infected persons reported pain/discomfort and 82.45% indicated limitations when performing usual activities, when evaluated 287 days (SD: 150) after the infection. Self-care was preserved in most post-COVID-19 persons, whereby only 13.16% indicated problems. The mean EQ5D-3L index score was 0.57 (SD: 0.23) and EQ5D VAS mean score was 56.6 (SD: 18.2). The mean index score for the normative population was significantly higher than for COVID-19 infected persons [mean difference of 0.31 (95% from 0.29 to 0.33), p < 0.01] while the mean score of chronic pain patients was significantly lower than the score of COVID-19 infected persons [mean difference of −0.31 (95% from −0.29 to −0.33), p < 0.01]. Compared to age-and sex adjusted reference data, health-related quality of life of persons with long COVID is severely impacted. In relation to patients with chronic pain after spinal surgery, the quality of life of post-COVID-19 infected persons seemed to be better. Clinical trial registration https://www.clinicaltrials.gov/, identifier: NCT04912778.